2012
DOI: 10.1186/1471-2202-13-156
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin protects against MPP+-induced oxidative stress in PC12 cells via the HO-1/NOX2 axis

Abstract: BackgroundAlthough the etiology of PD remains unclear, increasing evidence has shown that oxidative stress plays an important role in its pathogenesis and that of other neurodegenerative disorders. NOX2, a cytochrome subunit of NOX, transports electrons across the plasma membrane to generate ROS, leading to physiological and pathological processes. Heme oxygenase-1 (HO-1) can be rapidly induced by oxidative stress and other noxious stimuli in the brain or other tissues. Astaxanthin (ATX), a carotenoid with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…In summary, we found that ATX exerts neuroprotective effects against MPP + -induced cell death and suppression of ROS production via the the inhibition of Sp1/NR1 signal pathway activation. ATX may also activate other pathways or protect PC12 cells by alternate mechanisms [39], which would require further study. These results suggest that ATX may provide a valuable therapeutic strategy for the treatment of progressive neurodegenerative diseases such as Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we found that ATX exerts neuroprotective effects against MPP + -induced cell death and suppression of ROS production via the the inhibition of Sp1/NR1 signal pathway activation. ATX may also activate other pathways or protect PC12 cells by alternate mechanisms [39], which would require further study. These results suggest that ATX may provide a valuable therapeutic strategy for the treatment of progressive neurodegenerative diseases such as Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…The rat pheochromocytoma (PC12) cells have been extensively used as neuronal in vitro model as these cells share features with dopaminergic neurons (Ye et al 2012;Dong et al 2014;Wei et al 2014). H 2 O 2 is produced at nearly every stage of enzymatic oxidase action and applied widely as an inducer of neuronal oxidative stress in vitro (Zheng et al 2014;Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar experiment, astaxanthin treatment mitigated cytotoxicity in PC12 cells from MPP+ induced cytotoxicity. MPP+ is a toxic metabolite of the dopaminergic neurotoxin MPTP used in experimental animal models of PD [71]. These cell culture results were corroborated by an in vivo study using astaxanthin to prevent the neurodegeneration in the SN in response to dose of MPTP (1 i.p.…”
Section: Therapeutic Potential Of Astaxanthinmentioning
confidence: 88%